A Comparison of the Smile Esthetic Understanding of Periodontists, Orthodontists, General Dentists, and Dental Students - Altindal, Dicle; Tunca, Yasemin (European Journal of Therapeutics, 2024)
Objective: The aim of this study was to evaluate smile esthetics among periodontists, orthodontists, general dentists, and dental students. Methods: The study consisted of five groups: periodontists, orthodontists, general dentists, fifth-year dental students, and fourth-year dental students. The evulaters used the Smile Esthetics Index (SEI) consisting of 10 items to analyze the natural smile photographs of 15 different individuals. One-way ANOVA was performed for the comparison of group means. The Duncan multiple comparison test was also used to identify different groups. Non-linear principal component analysis was performed to determine the configuration of the relationship between categories of variables in two-dimensional space. Results: The group with the highest reliability coefficient among the groups was the fourth-year dental students (Cronbach’s Alpha = 0.89). This was followed by general dentists, periodontists, fifth-year dental students, and orthodontists. According to the evaluation of the total score averages of the fifteen pictures, a statistically significant difference was observed between the groups (p = 0.041). Accordingly, the fourth-year dental students (5.78 ±1 .13) had a lower total score than the fifth-year dental students (6.56 ± 0.88), and this difference was statistically significant. However, no significant difference was observed between the fourth-year dental students and the general and specialized dentists and between the fifth-year dental students and graduated and specialized dentists in terms of the total score given to the pictures. Conclusion: It was observed that the reliability coefficient was high in all groups evaluated with SEI. It can be concluded that esthetic perception is formed by actively performing the profession of dentistry, and this situation does not change according to specialization.